Peer leadership in collaborative argumentative writing: A qualitative case study of blended design - Wu, Qian; Jin, Tan; Chen, Jing; Lei, Jun (Journal of second language writing, 2023)
Collaborating with peers enables learners to face up to challenges in argumentative writing. Leadership constitutes an integral part of peer collaboration. Nevertheless, putting learners in groups cannot ensure fruitful teamwork, especially in a blended learning context. To probe into peer leadership in blended collaborative argumentative writing, the current study adopted a qualitative approach and focused on leadership performances of five EFL learners. By analyzing group discussions, written products and semi-structured interviews, this case study examined how EFL learners performed leadership behaviors to facilitate collaborative argumentative writing during offline and online learning. Offline leadership was mainly employed to generate and develop claims, and elaborate upon sub-arguments, while online leadership helped clarify claims, pinpoint evidence and reasoning, synthesize sub-arguments and revise argument. Peer leadership fluctuated in terms of type, agent and argumentative focus across the offline and online contexts. Leadership performances in the two contexts intersected with and complemented each other to contribute to collaborative argumentative writing. These findings unpack the nature of leadership in collaborative argumentative writing, and reveal its fluidity within a blended learning design.